Magnetic Resonance Imaging “Tigroid Pattern” in Alexander Disease - Biancheri, Roberta; Rossi, Andrea; Ceccherini, Isabella; Pezzella, Marianna; Prato, Giulia; Striano, Pasquale; Minetti, Carlo (Neuropediatrics, 2013)
Alexander disease (AD) is a rare white matter disorder resulting from mutations in the gene encoding for the glial fibrillary acidic protein. Diffuse white matter involvement with frontal predominance is typical of infantile AD that is clinically characterized by progressive motor and mental retardation, seizures, and megaloencephaly. We describe the case of a 10-year-old patient harboring a de novo missense mutation c.235C > T (p.R79C) in the GFAP gene, showing a relatively slow clinical and neuroradiologic progression of disease associated with a previously unreported magnetic resonance imaging (MRI) finding consistent with the so-called tigroid pattern. This pattern has been previously described in only a few different neurologic conditions, including Pelizaeus-Merzbacher disease and some lysosomal disorders. This report expands the spectrum of MRI features in AD.
Keywords: Alexander disease; GFAP; tigroid pattern